The anthropology of the future - Bryant, Rebecca; Knight, Daniel M. (Cambridge University Press, 2019)
Anticipation -- Expectation -- Speculation -- Potentiality -- Hope -- Destiny
Includes bibliographical references and index
Keywords: Futurologie; Zukunftserwartung; Sozialanthropologie; Philosophische Anthropologie; Zukunft; Anthropologie; Future, The / Social aspects; Time / Social aspects; Expectation (Philosophy); Hope; Opportunity; Fortune